Public Participation in Municipal Planning and Development: South African Local Government Perspective - Lesedi Nkoane (International Journal of Law, Social Science, and Humanities, 2026)
This article aims to explore public participation in municipal planning and development, looking at South African Local Governments. Section 152(1)(e) of the Constitution of the Republic of South Africa 1996 governs how community members and community groups participate in local government to improve democracy. Local governments need to create a culture of governance that blends public participation with representative democracy. Nevertheless, community participation in local government has not led to the improvement of governance or the development of democracy since municipalities have not done enough to include communities in municipal matters. It is also argued that there is a disconnect between what rural community residents genuinely need and want through community dialogue and involvement programs and what the municipality is doing. Dissatisfaction with local governments is demonstrated by service delivery protests, which erode public authority and invalidate government practices and hinder the development of a culture of community involvement. The public's discontent with local governments is the cause, even though South Africa has sufficient legal requirements for public participation. The study adopted a qualitative method relying heavily on secondary data. The findings showed that, despite a lack of knowledge regarding municipal affairs, municipalities can achieve their maximum service delivery potential if they implement community engagement strategies. The paper concludes that an improved means of community participation and involvement in IDP processes is essential for service delivery. Key words: Public participation, Integrated development plan (IDP), Governance, Service Delivery.